An observational study: Correlation of serum calcium levels in relation to phototherapy in term newborns - Gupta, Lovish; Mandot, Sanjay; Goyal, Dileep (Indian Journal of Child Health, 2020)
Background: Hyperbilirubinemia is one of the most prevalent problems in neonates. Jaundice is observed during the 1st week of life in approximately 60% of term neonates and 80% of preterm neonates. Phototherapy is one of the routine methods for the management of hyperbilirubinemia. Objective: The objective of this study was to assess the effect of phototherapy on serum calcium levels in term newborns with neonatal hyperbilirubinemia. Materials and Methods: Full-term newborns admitted in the postnatal ward with hyperbilirubinemia were included in the study population. Serum calcium estimation was done before phototherapy and all newborns were subjected to double surface phototherapy. After 24–48 h of phototherapy, serum calcium was estimated again and compared with the earlier value. Results: A total of 50 newborns were included in the study. After phototherapy, serum calcium levels were 7.31–7.60 mg/dl in 20 newborns, 7.61–7.90 mg/dl in 19 newborns, 7.0–7.30 mg/dl in 7 newborns, and 7.91–8.20 mg/dl in 4 newborns. This reduction in calcium level was found to be statistically significant (p